Chinese currency Renminbi, really undervalued? - Štembera, Jaroslav; Mičúch, Marek, 1980-; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
The thesis focuses on the question of undervaluation of the renminbi exchange rate to the U.S. dollar from the perspective of three selected alternative methods of calculating long term equilibrium exchange rate. In the case of calculations of behavioral equilibrium exchange rate and the natural real exchange rate, I performed calculations by using vector error correction model. In the case of fundamental equilibrium exchange rate I used error correction model. The input data used in the models are ranging from 1980 to 2010. Those are primarily value of nominal exchange rates, price levels and foreign trade. According to my results behavioural and fundamental equilibirum exchange rate show undervaluation of the renminbi to the year 2010, while the natural real exchange rate indicates a slight overvaluation of the renminbi to the year 2010.
Vedoucí práce: Marek Mičúch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses